Estudos taxonômicos e anatômicos em Imperata Cirillo (Poaceae - Andropogoneae) - Pinto, Bianca Leticia de Souza (2023)
Poaceae is the Angiosperm family with the greatest economic importance in the world. Its cosmopolitan distribution is favored by the great variability and versatility of its species. Imperata is a genus of Poaceae that is part of the tribe Andropogoneae and includes about 13 species found mainly in tropical and subtropical regions. For Brazil, four species were listed: I. brasiliensis, I. contracta, I. minutiflora, and I. tenuis. Like other genera of the tribe, Imperata has species with uncertain delimitation. Anatomical and micromorphological studies, as well as the correct definition of the type materials of the species, have been shown to be useful in the circumscription of taxa in Andropogoneae. The objective of this study was to perform a taxonomic treatment for the species of Imperata that occur in Brazil, designating lectotypes for species of the genus that presented typification problems. Anatomical and micromorphological foliar characters and anatomical characters of the stem were also described in order to help the taxonomy of the group. The taxonomic treatment involved a revision of the main Brazilian herbaria. The lectotypifications were made by consulting the bibliography and online collections of herbaria around the world. The description of anatomical and micromorphological characters was performed with usual techniques of anatomy and scanning microscopy. Altogether, lectotypes were designated to five names of Imperata: I. arundinacea var. americana, I. brasiliensis, I. brasiliensis var. americana, I. brevifolia, and I. minutiflora. With the taxonomic treatment, the occurrence of three species for Brazil was confirmed (I. brasiliensis, I. contracta, and I. tenuis) and it was concluded that I. minutiflora does not occur in the country. An identification key to the confirmed species was proposed, in addition to detailed descriptions with illustrations. The anatomical characters proved to be of high taxonomic value, highlighting the presence of papillate cells on the leaf blade, as well as two lignified sheaths around the vascular bundles as strong characteristics for the genus. Furthermore, it was noted that all species have aerenchyma cavities in the leaf sheaths and that stem internodes are hollow. At the interspecific level, features such as stomatal guard cell morphology and trichome classification proved useful in helping to differentiate Imperata species.